Prediction of incident heart failure by serum amino‐terminal pro‐B‐type natriuretic peptide level in a community‐based cohort. (18th January 2019) - Campbell, Duncan J.; Gong, Fei Fei; Jelinek, Michael V.; Castro, Julian M.; Coller, Jennifer M.; McGrady, Michele; Boffa, Umberto; Shiel, Louise; Wang, Bing H.; Liew, Danny; Wolfe, Rory; Stewart, Simon; et al.
Abstract : Aims: We investigated which serum amino‐terminal pro‐B‐type‐natriuretic peptide (NT‐proBNP) levels inform heart failure (HF) risk in a community‐based population at increased cardiovascular disease (CVD) risk. Methods and results: Inclusion criteria were age ≥ 60 years with one or more of self‐reported hypertension, diabetes, heart disease, abnormal heart rhythm, cerebrovascular disease, or renal impairment. Exclusion criteria were known HF, ejection fraction (EF) < 50%, or more than mild valve abnormality. NT‐proBNP levels were measured in 3842 participants on enrolment. HF was diagnosed in 162 participants at a median of 4.5 (interquartile range 2.7–5.4) years after enrolment, 73 with HF with preserved EF (HFpEF), 53 with HF with reduced EF (HFrEF), and 36 with valvular HF (VHF). Areas under the receiver operating characteristic curve (AUC) for 5‐year prediction of total HF were similar for NT‐proBNP alone (0.79, 95% confidence interval 0.74–0.83) and a 7‐parameter multivariable model (0.82, 0.77–0.86, P  = 0.035). NT‐proBNP cut‐points of 11, 16, and 25 pmol/L for individuals aged 60–69, 70–79, and ≥ 80 years, respectively, achieved sensitivities > 76% and specificities of 47–69% for 5‐year prediction of total HF in men and women in all three age groups. Sensitivities were ≥ 75% in most subgroups according to body mass index, estimated glomerular filtration rate, and the presence or absence of atrial fibrillation, pacemaker, or CVD, and for the prediction of HFpEF, HFrEF and VHF. Conclusion: Age‐specific serum NT‐proBNP levels inform prognosis, and hence therapeutic decisions, regarding HF risk in individuals at increased CVD risk.